2018
DOI: 10.1021/acs.inorgchem.8b01775
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic CO2 Reduction with Cis and Trans Conformers of a Rigid Dinuclear Rhenium Complex: Comparing the Monometallic and Cooperative Bimetallic Pathways

Abstract: Anthracene-bridged dinuclear rhenium complexes are reported for electrocatalytic carbon dioxide (CO) reduction to carbon monoxide (CO). Related by hindered rotation of each rhenium active site to either side of the anthracene bridge, cis and trans conformers have been isolated and characterized. Electrochemical studies reveal distinct mechanisms, whereby the cis conformer operates via cooperative bimetallic CO activation and conversion and the trans conformer reduces CO through well-established single-site and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 93 publications
4
60
1
1
Order By: Relevance
“…It was concluded that the build-up of HCO3-/CO32- during bulk electrolyses resulted in precipitation of the complexes as HCO3- or CO32- salts (Chen et al, 2011; Elgrishi et al, 2014). We confirmed the formation of carbonate in CPE experiments with boldCoLbold2bold2bold+ by barium triflate titration (Yang et al, 2018), consistent with the reductive disproportionation of CO 2 to CO and CO32-. The use of DMF solved this solubility issue as no precipitate was observed during electrolyses over extended periods of time.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It was concluded that the build-up of HCO3-/CO32- during bulk electrolyses resulted in precipitation of the complexes as HCO3- or CO32- salts (Chen et al, 2011; Elgrishi et al, 2014). We confirmed the formation of carbonate in CPE experiments with boldCoLbold2bold2bold+ by barium triflate titration (Yang et al, 2018), consistent with the reductive disproportionation of CO 2 to CO and CO32-. The use of DMF solved this solubility issue as no precipitate was observed during electrolyses over extended periods of time.…”
Section: Resultssupporting
confidence: 83%
“…The turnover frequency (TOF) of boldCoLbold2bold2bold+ was calculated as previously described (Narayanan et al, 2016; Yang et al, 2018) from scan rate-dependent linear sweep voltammograms performed in N 2 - and CO 2 -saturated solutions containing 5% H 2 O. A plot of the i cat / i p current ratio at different scan rates as a function of potential is shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…The development of bimetallic Re complexes based on Re(bpy)(CO) 3 X and its derivatives has been of recent interest for both photocatalytic (Bruckmeier et al, 2012) and electrocatalytic processes due to the concentration-dependent formation of binuclear intermediates as part of the catalytic cycle (Machan et al, 2014a, 2016; Wilting et al, 2017; Yang et al, 2018). In electrocatalytic systems, the first bimolecular Re system studied utilized acetoamidomethyl modified bpy to generate a supramolecular catalyst system in situ .…”
Section: Enzymes For the Interconversion Of Co2 And Co Or Formic Acidmentioning
confidence: 99%
“…Work to generate rigid homobimetallic Re(bpy)(CO) 3 X systems where the metal centers are in close proximity has been achieved using an anthracene linker by Jurss and co-workers (Yang et al, 2018). This complex can be isolated as cis or trans isomers through chromatography, which alters the relative positioning of the Re centers (Yang et al, 2018). The cis isomer, in which the Re centers are in close proximity to one another, outperformed both a monometallic anthracene control complex and the trans isomer of the homobimetallic species in catalytic studies.…”
Section: Enzymes For the Interconversion Of Co2 And Co Or Formic Acidmentioning
confidence: 99%
“…20,98103 A characteristic of an unstable metal carboxylate is extreme Brønsted basicity (high {p K a3 }), which has been observed in some catalytic systems that scavenge protons from adventitious water or electrolyte. 104107 If protonation and reduction of the metal carboxylate (intermediate B) is successful in cleaving a C–O bond, more electron-rich metals will result in a greater energetic barrier for CO release (intermediate C).…”
Section: Co Productionmentioning
confidence: 99%